THE IMPACT OF STRESS ON ACADEMIC PERFORMANCE OF FIRST-YEAR MEDICAL STUDENTS - S, SUBHALAKSHMI; NS, SASIKUMAR; GANESH T, AMIRTHAMANI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: Anxiety is not uncommon in students pursuing professional and other courses. It makes us tired very early, as well as becoming the main cause of stress in young adults. Cognitive function may be affected during or after a stressful event. Our primary objective is to determine the prevalence of anxiety among medical students at Tirunelveli Medical College (TVMC), Tirunelveli. Methods: A cross-sectional study was carried out among 150 1st-year medical students of TVMC who had spent more than 6 months in college. We assessed the students during the period without and during the period with examinations. Anthropometric variables of students included are age, gender, weight, height, and body mass index. The prevalence of anxiety was determined with a structured, validated questionnaire. We used the Hamilton Anxiety Scale (HAM-A), which has a cut-off score for various levels of anxiety. The students were subjected to the questionnaire both before and during the examination. All 150 students completed the questionnaire. Anthropometric parameters are age-matched. Results: Data were analyzed using a paired “t” test. A high prevalence of anxiety (p<0.001) among medical students was found. Conclusion: Female students were found to be more prone to anxiety than male students, and there was a significant association between the prevalence of anxiety and the examination period. This study finds a significant number of students with high anxiety scores indicating emotional distress, which may result in poor academic performance.